Implementasi Agile Method untuk Pengembangan Sistem Pembatasan Pengunjung Wisata Berbasis Mobile - Noviandi Noviandi; Nanda Aula Rumana (Journal of Information System Research (JOSH), 2022)
The high number of Covid-19 patients in 2021 has an impact on the tourism sector. It changes the trend towards tourism in Indonesia. Apart from the health protocols that must be carried out, the role of technology is also important in overcoming the growth of Covid-19. The technology provided is in the form of an application to purchase tourist entrance tickets, but it does not yet provide the menu for tourist restriction and zone identification. The purpose of this research is to develop an information system that can limit the number of tourists and find out the red zone (the highest Covid-19 area) before making a tourist visit. The method used for the development of a tourist visitor information system is the Agile model. This model is carried out systematically and starts from collecting information with interview and observation techniques, needs analysis, system design, design, and the implementation using an object-oriented diagram approach. This model has complex capabilities, is reliable, and produces applications in a short time. The testing of the tourist restriction system uses black box testing. The goal is to find out the error when the system is used by end users. Test results on all features in the system according to the needs of the end user. The application built can be used in line with the government rules or policies. With this application, the tourists are expected to be able to have vacation without the risk of spreading Covid-19.